Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1515/amm-2017-0199
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Material Coating on the Heat Transfer in a Layered Cu-SiC-Cu Systems

Abstract: This paper describes the process of obtaining Cu-SiC-Cu systems by way of spark plasma sintering. A monocrystalline form of silicon carbide (6H-SiC type) was applied in the experiment. Additionally, silicon carbide samples were covered with a layer of tungsten and molybdenum using chemical vapour deposition (CVD) technique. Microstructural examinations and thermal properties measurements were performed. A special attention was put to the metal-ceramic interface. During annealing at a high temperature, copper r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Strojny-Nędza A, et al studied SiC/Cu composites using spark plasma sintering, and Cu-SiC-Cu systems were obtained after processing. They found that the copper reacts with the silicon carbide (6H-SiC type) during the process of annealing at high temperature [32]. According to the above, SiC/Cu interfacial investigations are crucial to the properties of the SiC/Cu composites.…”
Section: Introductionmentioning
confidence: 99%
“…Strojny-Nędza A, et al studied SiC/Cu composites using spark plasma sintering, and Cu-SiC-Cu systems were obtained after processing. They found that the copper reacts with the silicon carbide (6H-SiC type) during the process of annealing at high temperature [32]. According to the above, SiC/Cu interfacial investigations are crucial to the properties of the SiC/Cu composites.…”
Section: Introductionmentioning
confidence: 99%
“…Chen, G.Q et al found that layered interfacial products were consisted by SiC particles, a Cu-Si layer, a polycrystalline C layer and Cu-Si matrix, but no CuSi3 product was detected in these reacted regions [31]. Strojny-Nędza A, et al studied the SiC/Cu composites by using the spark plasma sintering and Cu-SiC-Cu and systems were obtained, and they found that the copper reacts with the silicon carbide (6H-SiC type) during the processing of the annealing at a high temperature [32]. According to the discussions above, it can be found that the SiC/Cu interfacial investigation is very crucial to the properties of the SiC/Cu composites.…”
Section: Introductionmentioning
confidence: 99%